POTENTIAL AND FEASIBILITY ANALYSIS OF BIOMASS ENERGY FROM PALM OIL MILLS ON NORTH PENAJAM PASER REGENCY REGION OF THE NEW STATE CAPITAL INDONESIA - Faruq Nashrulloh; Muhammad Sulaiman; Rachmawan Budiarto (Master in Systems Engineering, 2020)
This paper presents a techno-economic potential and feasibility analysis on the planning of Biomass renewable energy from palm oil mills on the North Penajam Paser Regency. They were analyzed using the last three years of production data history from 7 Palm oil Processing Factories in the region and using questionnaires and interviews. Total processing fresh fruit brunch is about 891.624 tons/year. Total potential electricity generated from palm oil residue (Fiber, Shell, and Stem) is 28.009 kWh. The factories are located in Babulu, Waru, Penajam, and Sepaku.The assessment of sustainability indicators in this research is considering technology and economic aspects. The technology aspect evaluates the technical planning of installations that are possible to build in the area. For financial aspects of sustainability, evaluates the net present value (NPV), internal rate of return (IRR) and, the payback period of renewable energy installation. This analysis is used to get a comprehensive insight from the potential biomass energy at the research location and conduct a feasibility study based on techno-economic analysis to develop new state capital Indonesia and the supporting regions.